Cosolvent effects on solute-solvent hydrogen-bond dynamics: ultrafast 2D IR investigations - Kashid, Somnath M.; Jin, Geun Young; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry B, 2015)
Cosolvents strongly influence the solute-solvent interactions of biomolecules in aqueous environments and have profound effects on the stability and activity of several proteins and enzymes. Experimental studies have previously reported on the hydrogen-bond dynamics of water molecules in the presence of a cosolvent, but understanding the effects from a solute's perspective could provide greater insight into protein stability. Because carbonyl groups are abundant in biomolecules, the current study used 2D IR spectroscopy and molecular dynamics simulations to compare the hydrogen-bond dynamics of the solute's carbonyl group in aqueous solution, with and without the presence of DMSO as a cosolvent. 2D IR spectroscopy was used to quantitatively estimate the time scales of the hydrogen-bond dynamics of the carbonyl group in neat water and 1:1 DMSO/water solution. The 2D IR results show spectral signatures of a chemical exchange process: The presence of the cosolvent was found to lower the hydrogen-bond exchange rate by a factor of 5. The measured exchange rates were 7.50 X 10(11) and 1.48 X 10(11) s(-1) in neat water and 1:1 DMSO/water, respectively. Molecular dynamics simulations predict a significantly shorter carbonyl hydrogen-bond lifetime in neat water than in 1:1 DMSO/water and provide molecular insights into the exchange mechanism. The binding of the cosolvent to the solute was found to be accompanied by the release of hydrogen-bonded water molecules to the bulk. The widely different hydrogen-bond lifetimes and exchange rates with and without DMSO indicate a significant change in the ultrafast hydrogen-bond dynamics in the presence of a cosolvent, which, in turn, might play an important role in the stability and activity of biomolecules.

Two-dimensional infrared spectroscopy reveals cosolvent-composition-dependent crossover in intermolecular hydrogen bond dynamics - Kashid, Somnath M.; Jin, Geun Young; Chakrabarty, Suman; Kim, Yung Sam; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2017)
Cosolvents have versatile composition-dependent applications in chemistry and biology. The simultaneous presence of hydrophobic and hydrophilic groups in dimethyl sulfoxide (DMSO), an industrially important amphiphilic cosolvent, when combined with the unique properties of water, plays key roles in the diverse fields of pharmacology, cryoprotection, and cell biology. Moreover, molecules dissolved in aqueous DMSO exhibit an anomalous concentration-dependent nonmonotonic behavior in stability and activity near a critical DMSO mole fraction of 0.15. An experimental identification of the origin of this anomaly can lead to newer chemical and biological applications. We report a direct spectroscopic observation of the anomalous behavior using ultrafast twodimensional infrared spectroscopy experiments. Our results demonstrate the cosolventconcentration-dependent nonmonotonicity arises from nonidentical mechanisms in ultrafast hydrogen-bond-exchange dynamics of water above and below the critical cosolvent concentration. Comparison of experimental and theoretical results provides a molecular-level mechanistic understanding: a distinct difference in the stabilization of the solute through dynamic solute solvent interactions is the key to the anomalous behavior.

Interconverting hydrogen-bonding and weak n -> pi* interactions in aqueous solution: A direct spectroscopic evidence - Deb, Pranab; Jin, Geun Young; Singh, Santosh K.; Moon, Juran; Kwon, Hyejin; Das, Aloke; Bagchi, Sayan; Kim, Yung Sam (Journal of Physical Chemistry Letters, 2018)
Molecular structure and function depend on myriad noncovalent interactions. However, the weak and transient nature of noncovalent interactions in solution makes them challenging to study. Information on weak interactions is typically derived from theory and indirect structural data. Solvent fluctuations, not revealed by structure analysis, further complicate the study of these interactions. Using 2D infrared spectroscopy, we show that the strong hydrogen bond and the weak n -> pi* interaction coexist and interconvert in aqueous solution. We found that the kinetics of these interconverting interactions becomes faster with increasing water content. This experimental observation provides a new perspective on the existence of weak noncovalent interactions in aqueous solution.